Uji Potensi Daya Hambat Ekstrak Metanol Biji Jintan Hitam (Nigella Sativa L.) Terhadap Bakteri Streptococcus - Guntur Satrio Pratomo; Nurul Chusna; Muhammad Priyadi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
One of the plants that are often used as medicinal plants is Black Seed, Black Seed is a medicinal plant known in Indonesia by the name of black cumin. Black cumin seeds and essential oils (Nigella sativa L.) have been widely used in traditional medicine. Many studies have proven the effects of Nigella sativa extract. In various studies, black cumin seed oil shows efficacy as an anti-cancer, anti-free radical and immunomodulator, analgesic, antimicrobial, anti-inflammatory, a spasmolytic, bronchodilator, hepatoprotective, and anti-hypertensive Advanced chemical analysis found that Black Seed contains carotene that is converted into vitamin A by heart. The purpose of this study was to determine the potential inhibition of methanol extract of black cumin seeds (Nigella Sativa L.) against Streptococcus. This research uses a quantitative approach with an experimental method. This research was conducted in the Pharmacognition and Microbiology Laboratory of the Faculty of Health Sciences, Muhammadiyah University, Palangkaraya. The sample used was a sample of plant material, namely Black Cumin Seed (Nigella sativa L) which had been dried and pollinated and then extracted and then tested against bacteria. The results of testing the antibacterial activity showed that from low concentration to high concentration the diameter of the resulting inhibition showed that the activity could inhibit the bacteria streptococcus mutants. The highest inhibition at a concentration of 6% is 0.83 mm and the lowest concentration at a concentration of 3% against Streptococcus mutants.